REFLEKSI NILAI ADAB DAN HUBUNGAN HORIZONTAL DALAM NASKAH BABAD AWAK SALIRA - Isep Bayu Arisandi; Titin Nurhayati Ma’mun; Undang Ahmad Darsa (Jurnal Lektur Keagamaan, 2021)
ABSTRACT The value of moral affects the horizontal relationship that exists between humans. This is recorded in the ancient texts of the Islamic period as evidence of the influence of Islamic teachings that entered the archipelago. The disclosure of this moral value is an effort to "share" the heritage of the ancestors, as well as a reflection on the current conditions that are quite relevant. The Babad Awak Salira (BAS) manuscript, one of the written heritages in Tatar Sunda, contains very strong moral values. The problems revealed in this paper, namely; (1) the values ​​of moral contained in the text of the BAS manuscript; and (2) the effect of moral reflection in the horizontal relationship. This paper aims to reveal the values ​​of moral and their influence on horizontal relationships. This research is a literature research, descriptive analysis. Due to the fact that the object is an ancient text, a philological approach is used to study the BAS text. Seeing this, the relevance of the existence of values ​​in the ancient texts (which are time apart) is so eternal in didactic wraps. The existence of content values ​​can also be seen as a piece of advice and a "treasure" of inheritance in a written tradition in Tatar Sunda, in general in the archipelago. Disclosure of the value of the content of ancient manuscripts, can be seen as an effort to understand and "bridge" the times, considering that the medium of script is no longer conventional at this time. Keywords: Manuscript, Text BAS, Moral values, Moral reflection.   Nilai adab berpengaruh terhadap hubungan horizontal yang terjalin antarmanusia. Hal ini tercatat dalam naskah kuna periode Islam sebagai bukti pengaruh ajaran Islam yang masuk ke Nusantara. Pengungkapan nilai adab ini sebagai upaya “membagikan” warisan nenek moyang, juga sebagai refleksi atas kondisi zaman saat ini yang cukup relevan. Naskah Babad Awak Salira (BAS), salah satu warisan tulis yang ada di Tatar Sunda, mengandung nilai-nilai adab yang kuat. Masalah yang diungkap dalam tulisan ini, yaitu; (1) nilai adab yang ada di dalam teks naskah BAS; dan (2) pengaruh refleksi adab dalam hubungan horizontal. Tulisan ini bertujuan untuk mengungkap nilai-nilai adab dan pengaruhnya terhadap hubungan horizontal. Kajian berjenis studi pustaka, bersifat deskriptif analisis. Sehubungan bahwa objek adalah naskah kuna, digunakan pendekatan filologis untuk mengkaji naskah BAS. Melihat hal itu, relevansi keberadaan nilai dalam naskah kuna (yang berjarak zaman) begitu kekal dalam balutan didaktis. Keberadaan nilai kandungan juga dapat dipandang sebagai sebuah petuah dan “harta” warisan dalam sebuah tradisi tulis di Tatar Sunda, secara umum di Nusantara. Pengungkapan nilai kandungan naskah kuna dapat dilihat sebagai upaya memahamkan dan “menjembatani” zaman, mengingat medium aksara sudah tidak konvensional lagi saat ini. Kata kunci: Naskah kuna, Teks BAS, Nilai Adab, Refleksi Adab.